An improvement of some inequalities similar to Hilbert's inequality - Young-Ho Kim (International Journal of Mathematics and Mathematical Sciences)
We give an improvement of some inequalities similar to Hilbert's inequality involving series of nonnegative terms. The integral analogies of the main results are also given.